2020
DOI: 10.1029/2019jd031286
|View full text |Cite
|
Sign up to set email alerts
|

A Large Ensemble Approach to Quantifying Internal Model Variability Within the WRF Numerical Model

Abstract: The Weather Research and Forecasting (WRF) community model is widely used to explore cross‐scale atmospheric features. Although WRF uncertainty studies exist, these usually involve ensembles where different physics options are selected (e.g., the boundary layer scheme) or adjusting individual parameters. Uncertainty from perturbing initial conditions, which generates internal model variability (IMV), has rarely been considered. Moreover, many off‐line WRF research studies generate conclusions based on a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Additionally, MOSAIC treats the processes of aerosol nucleation, coagulation, condensation, water uptake, and aqueous chemistry. Aerosol dry deposition is handled via the method in Binkowski and Shankar (1995), which includes Brownian and turbulent diffusion as well as gravitational settling. Wet deposition of aerosols and gases Figure 1.…”
Section: Wrf-chemmentioning
confidence: 99%
“…Additionally, MOSAIC treats the processes of aerosol nucleation, coagulation, condensation, water uptake, and aqueous chemistry. Aerosol dry deposition is handled via the method in Binkowski and Shankar (1995), which includes Brownian and turbulent diffusion as well as gravitational settling. Wet deposition of aerosols and gases Figure 1.…”
Section: Wrf-chemmentioning
confidence: 99%
“…However, RACM17 shows higher correlation coefficients compared to MOZ17 at other stations. Although the difference in the correlation coefficients for the different chemistry mechanism is small, it is likely due to radiation feedbacks between the chemistry and meteorology in these mechanisms and internal model variability (Bassett et al, 2020). Furthermore, the temperature bias between the observed and simulated datasets is below 3 • C at all stations (Table 3), and all of the data points lie in close proximity to the one-to-one lines.…”
Section: Surface Meteorologymentioning
confidence: 84%
“…8d). We believe this to be the result of internal model variability rather than a physical manifestation (Bassett et al 2020). Examination of several grid points where the March-through-June mean SWE anomalies were positive revealed that fine-scale storm location and intensity differences between, for instance, CNT and noBCSDE were leading to positive SWE anomalies (not shown).…”
mentioning
confidence: 94%